‘The Early Exposure is Really Helpful’ – Students’ Views of Participating in Communication Skills Screening - Johnson, Robyn; Purcell, Alison; Power, Emma; Cumming, Steven (International Journal of Practice-based Learning in Health and Social Care, 2021)
Students commence university with many hopes and dreams for their future and for most, these are realised. Health professional students must succeed in both their academic and clinical experiences. Excellent communication with their patients and colleagues on placement is necessary and particularly so for speech pathology students. This qualitative, descriptive study investigates how first- and final-year students view the screening of their communication skills in which they participate. The focus groups took place within the speech pathology department of a major Australian metropolitan university. Data were transcribed and analysed thematically. Three main themes arose: professional development, students’ cognitive and emotional responses, and the organisation of the screener. Both groups of students felt the screener was both an important part of their professional development and a way of identifying and supporting speech pathology students with communication difficulties. They valued the student-led nature of the process. Implications for the value of using a student-led communication screener to identify students with weaker communication skills early in their program and for the support of such students are discussed.